Global prevalence of frailty in hemodialysis patients: a systematic review and meta-analysis - Xiang, Ying; Tong, Jia-Le; Qian, Weiwei; Deng, Peng (Frontiers in Medicine, 2025)
BackgroundThe coexistence of frailty and hemodialysis is associated with a higher risk of adverse health outcomes, including hospitalization, mortality, and falls. Although the estimated prevalence of frailty in hemodialysis patients is widely reported, the results vary significantly across the relevant literature. Currently, comprehensive evidence regarding the global prevalence of frailty among hemodialysis patients remains unknown.ObjectiveIn this systematic review and meta-analysis, our primary objective was to determine the global prevalence of frailty among hemodialysis patients, while accounting for stratification by sample size, age, duration of hemodialysis, gender, publication year, diagnostic criteria, and region.DesignA systematic review and meta-analysis.Data sourceCochrane Library, Medline, PubMed, Embase, Web of Science, Scopus, CINAHL, China Knowledge Resource Integrated Database (CNKI), Wanfang Database, Chinese Biomedical Database (CBM), and Weipu Database (VIP) from inception to 15 June 2023.MethodsOriginal articles that evaluated the prevalence of frailty in hemodialysis patients were included. Data extraction and methodological quality assessment of the included studies were performed independently by two reviewers. The pooled prevalence of frailty was estimated using the random-effects model. Meta-regression analysis and subgroup analysis were undertaken to explore sources of heterogeneity.ResultsA total of 64 studies from 10 different countries met the inclusion criteria, with a total sample of 23,799 hemodialysis patients. The global pooled prevalence of frailty in hemodialysis patients was 39.6% (95%CI 35–44%), with significant heterogeneity across the various studies. The subgroup analysis results demonstrated that the prevalence of frailty among hemodialysis patients varied significantly based on sample size, age, duration of hemodialysis, gender, publication year, diagnostic criteria, and geographic region. Meta-regression showed that factors such as sample size, age, and gender independently emerged as predictors of frailty prevalence.ConclusionHigh frailty prevalence was found in patients on hemodialysis, which may lead to poor health outcomes. The current analysis suggests that risk factors for frailty in hemodialysis patients should be further investigated in future studies, and early screening and interventions for frailty should be incorporated into the routine care of hemodialysis patients to reduce the negative impact of frailty.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023411983, identifier PROSPERO (CRD42023411983).